2022
DOI: 10.21203/rs.3.rs-1812865/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying and prioritizing Sediment-prone areas at the sub-basin level of Tekeze watershed, Ethiopia

Abstract: Soil erosion is a serious concern around the world because of its detrimental effect on agricultural productivity and reservoir storage capacity, which is mostly caused by improper land management. Effective land management entails expensive soil conservation measures which are not affordable in developing countries, especially in large watersheds. Thus, identifying the most vulnerable areas for sediment yield and executing remedial measures for those areas is critical to lower costs and maintain effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The application of the SWAT model for the study of water resources and environmental assessments has shown significant progress in Africa [25]. The SWAT model application in Ethiopia is also progressive but limited to a few major river basins which have ground-measured data [26][27][28][29][30]. Hydrological modeling through SWAT is rare in ungauged basins due to a lack of data.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the SWAT model for the study of water resources and environmental assessments has shown significant progress in Africa [25]. The SWAT model application in Ethiopia is also progressive but limited to a few major river basins which have ground-measured data [26][27][28][29][30]. Hydrological modeling through SWAT is rare in ungauged basins due to a lack of data.…”
Section: Introductionmentioning
confidence: 99%